Design of in vitro model to study oral aroma release: Experimental study and numeric simulation of heat transfer in a foamed dairy matrix. (August 2020) - Thomas, Christine F.; Thienel, Katharina J.F.; Stefan, Thorsten; Schmidt, Christian M.; Hinrichs, Jörg
Abstract: Since aeration can increase aroma perception, it may be used to compensate the perceived aroma loss of low-fat dairy products. To be able to study the effect of aeration on aroma release systematically in the future, a temperature study was conducted on an in vitro model built to study aroma release at temperatures relevant for oral processing. The studied dairy foam contained 4% (w/w) milk protein and 0.75% (w/w) alginate and had a gas volume fraction of 71% after whipping. The temperature development during incubation of the foam at 40 °C was calculated using a numeric simulation. Thermal equilibrium was reached after 50 min. Sampling for dynamic aroma release was found to be ideal at 2, 7 and 15 min, because mean foam temperatures were 25, 30 and 35 °C. Experimental temperature analysis of the foam core was in good agreement with the simulation (R 2  = 0.95). Highlights: Model to study in vitro aroma release from a foamed dairy matrix was built. Temperature development in model during incubation at 40 °C was studied. Numeric model was validated successfully (R 2  = 0.95) using experimental data. Thermal equilibration at 39 °C was reached after 50 min of incubation. Dynamic aroma release studies will be performed at 2, 7 and 15 min of incubation.